Analysis of the techniques performed in a taekwondo university championship - Menescardi, C.; Estevan, I. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The aim of this study was to analyze the performance of taekwondo athletes according to the medal obtained (golden, silver, bronze and non-medalists) in a Spanish University Championship (2011), with emphasis on the kicking zone, the trajectory and the kicking leg. Methods: 356 performs of 178 bouts were analyzed: golden (n = 54), silver (n = 49), bronze (n = 71) and non-medalists (n = 182). The variables analyzed were: i) kicking zone (trunk or head), ii) trajectory (linear, circular or with previous spin), and iii) kicking leg (right or left). Only one observer was involved in the study. Intraobserver measures were reliable with an ICC = 0.85 (p < 0.01). According to the Belmont Report, because the analyzed video tapes are in the public domain, no participant`s informed consent was required. A previous K-S test was carried out to determine non-parametrical tests (Kruskall Wallis test followed by Mann Whitney U test for pair comparisons were conducted) (p < 0.05). Results: There were differences in linear techniques ( 2[3] = 58.762, p = 0.01), and right leg ( 2[3]= 9.041, p = 0.03). That is, medalists (golden [G], silver [S] and bronze [B]) performed more linear actions (G = 5.93±6.96, S = 6.43±4.52, B = 5.37±3.75) than non-medalists ([U = 3524.00], [U = 1965.50], and [U = 3235.00]; p = 0.01, respectively) who performed 2.70±3.38 actions. With regard to the kicking leg, non-medalists performed more actions with right leg (17.51±10.00) than golden medalists (14.20±8.62) (U = 3909.000; p = 0.02). No differences were found in variables related to the kicking zone (p > 0.05). Discussion: Results of the current study showed that medalists performed more linear actions and fewer actions with right leg (golden medalists) than non-medalists. Medalists could use linear techniques due to the major speed of these techniques than other ones (e.g., circular) (Leel et al., 2005) which could lead the victory. These results pointed out also the major ability of golden medalists to perform fewer techniques with right leg assuming the capability to perform techniques using both legs. These results could lead to a reorientation of technical-tactical training of taekwondo athletes to deal with actions linked to medalists.